Relationship between health literacy and quality of colonoscopy bowel preparation - Erdoğdu, Umut Eren; Çaycı, Hacı Murat; Tardu, Ali; Arslan, Ufuk; Demirci, Hakan; Yıldırım, Çınar (Turkish Journal of Gastroenterology, 2020)
Background/Aims: There are a variety of factors that affect the quality of colonoscopy bowel preparations, although the relationship between the level of health literacy (HL) and the quality of bowel preparations has yet to be clarified. The present study evaluated the effect of HL on the quality of bowel preparation prior to a colonoscopy. Materials and Methods: The data of 150 patients who underwent a colonoscopy for colorectal cancer screening and in whom the quality of bowel preparation was scored during the colonoscopy were recorded prospectively. The European Health Literacy Survey Questionnaire (HLS-EU-Q47) was used to evaluate HL prior to the colonoscopy, and the Boston bowel preparation scale was used to evaluate the quality of the bowel preparation during the colonoscopy. The demographic characteristics of the patients, the presence of comorbidities, socioeconomic characteristics (marital status, income level, and educational level), HLS-EU-Q47 questionnaire, and Boston bowel preparation scale scores were recorded and evaluated. Results: A significant linear relationship was identified between the general HL index score, the cleanliness of the colonic segments (right, transverse, and left colon) and the total Boston bowel preparation scale score (p=0.013, p=0.010, p=0.008, p=0.001, respectively). In a HL subgroup analysis, a significant linear relationship was noted between disease prevention and health promotion index, the cleanliness of the colonic segments (right, transverse, and left colon), and the total Boston bowel preparation scale score. It was observed that an increase in the health care index resulted in an increase in the cleanliness of the relevant colonic segments and the total Boston bowel preparation scale score. No relationship was found between the right, transverse, and left colon and the total Boston bowel preparation scale scores and gender, age, Body Mass Index (BMI), comorbidity, marital status, level of income, or educational level. Conclusion: The level of HL affects the quality of colonoscopy bowel preparations.